2015
DOI: 10.1111/nph.13504
|View full text |Cite
|
Sign up to set email alerts
|

Sustained exposure to abscisic acid enhances the colonization potential of the mutualist fungus Piriformospora indica on Arabidopsis thaliana roots

Abstract: SummaryRoot colonization by the beneficial fungus Piriformospora indica is controlled by plant innate immunity, but factors that channel this interaction into a mutualistic relationship are not known. We have explored the impact of abscisic acid (ABA) and osmotic stress on the P. indica interaction with Arabidopsis thaliana.The activation of plant innate immunity in roots was determined by measuring the concentration of the phytoalexin camalexin and expression of transcription factors regulating the biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 98 publications
1
26
0
Order By: Relevance
“…Hormonal regulation has been described to accompany the colonization of P. indica on A. thaliana roots [ 22 , 23 , 24 , 32 , 33 , 34 , 35 ]. An enrichment analysis ( Table 1 and Supplementary Table S1 ) of the upregulated root transcripts 14 dpi as published in Lahrmann et al [ 24 ] revealed an overrepresentation of genes involved in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway “Biosynthesis of plant hormones” (ath01070).…”
Section: Resultsmentioning
confidence: 99%
“…Hormonal regulation has been described to accompany the colonization of P. indica on A. thaliana roots [ 22 , 23 , 24 , 32 , 33 , 34 , 35 ]. An enrichment analysis ( Table 1 and Supplementary Table S1 ) of the upregulated root transcripts 14 dpi as published in Lahrmann et al [ 24 ] revealed an overrepresentation of genes involved in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway “Biosynthesis of plant hormones” (ath01070).…”
Section: Resultsmentioning
confidence: 99%
“…The phytohormone ABA plays a crucial role in adaptive responses to environmental stresses, as higher ABA expression in response to drought and high salinity induces massive changes in gene expression resulting in stomatal closure 31 , 121 . An overexpression mutant of a homolog of an ABA responsive gene that was upregulated in our data (Supplementary Tables S5 and S7 ), ATbetaFruct4, showed higher levels in leaf stomatal guard cells and led to increased drought tolerance in Arabidopsis 80 .…”
Section: Discussionmentioning
confidence: 99%
“…The production and signaling of the phytohormones ethylene, jasmonic acid (JA), gibberellic acid (GA), salicylic acid (SA) and abscisic acid (ABA) have all been shown to be impacted by P . indica 29 31 . Changes in levels of these hormones likely mediate abiotic stress responses 13 , 32 as well as regulate biotic responses such as induced and systemic plant defense responses, microbe-associated molecular patterns (MAMP) triggered immunity 6 , 29 , 33 , and autoregulation of mutualistic symbionts 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Connecting plants by a P. indica hyphal network resulted in elevated ABA levels and expression of ABA-responsive genes in non-infested plants (Figure 6 , Table 1 ). Also Peskan-Berghöfer et al ( 2015 ) showed that elevated ABA levels triggered by osmotic stress promoted P. indica colonization of the roots, without impairing plant fitness. Furthermore, sustained exposure to ABA muted defense response in roots and thereby made them more accessible for the mutualist.…”
Section: Discussionmentioning
confidence: 99%